Kontribusi Keputusan Operasi dalam Pencapaian Keunggulan Bersaing Biaya Rendah (Low Cost) pada Monica Collection Semarang - Veronica Kusdiartini; Agustine Eva Maria Soekesi; Meniek Srining Prapti; Bayu Perstianto (JEMAP, 2020)
This research result gives contribution to Decision on Operation in achieving  Low Cost Competitive Advantage in Monica Collection Semarang. Realizing this objective, it should be conducted research in operation decision supporting Monica Collection company to achieve its competitive advantage based on low cost. In this research it was found that there was operation decision conducted which supporting this low cost competitive advantage.